Urethritis in Males at Sexual Active Age (Detection of the Most Common Pathogen) - نداف لؤي; يوسف محمد; عثمان علي (Latakia University Journal -Medical Sciences Series, 2020)
Urethritis is defined as a clinical syndrome whose symptoms include Dysuria, Frequency, Urgency, and sometimes suprapubic pain. Urethritis can be classified into two main types, the first type is called Gonococcal urethritis (G.U) caused by Neiseria gonorrhoea, and the second type is called Non-gonococcal urethritis (N.G.U) caused by other organisms, such as (Clamydia trachomatis, Ureaplasma, Trichomonas vaginalis, Herpes simplex virus and Candida albicans). The patient with urethritis may complain of urethral discharge associated with dysuria, and the amount of these urethral discharge ranges from several drops to large quantities. About 30% of patients with Gonococcal urethritis have accompained infection with Clamydia trachomatis. The study sample included 100 patients of reproductive age who reviewed the urogenital clinic at Tishreen university hospital in Latakia and who complained of symptoms of urethritis in the period between the beginning of September 2016 until the end of August 2017. The organisms causing urethritis were investigated in vitro, as we studied each of the following pathogens: (Neiseria gonorrhoea, Clamydia trachomatis, Ureaplasma urealeticum, Candida albicans, Trichomonas vaginalis and Herpes simplex virus). In our study we found that Gonococcal urethritis (G.U) caused by Nieseria gonorrhoea is the most common as in our study it reached 55% compared to 45% in favor of Non-gonococcal urethritis. In patients with Non-gonococcal urethritis we were able to isolate Clamydia trachomatis in 35.6% of cases and Ureaplasma urealeticum in 4.4% of cases, while we found a common infection of both Clamydia trachomatis ane Ureaplasma urealeticum in 11.1% of cases. In the remaining 44.4% of cases of Non-gonococcal urethritis we were unable to isolate a specific pathogen who was accaused of causing urethritis and we called these cases Idiopathic Non-gonococcal urethritis.